Morpho-physiological and biochemical changes in Syzygium cumini and Populus deltoides: a case study on young saplings under water stress - Zafar, Zikria; Rasheed, Fahad; Khan, Waseem Razzaq; Afzal, Shazia; Abdual Qadeer; Muhammad Mohsin; Mohd Nazre; Raza, Zohaib; Ibrahim, Faridah Hanum (MDPI, 2021)
Drought is one of the most devastating climate factors in terms of its spatial extent and intensity. Therefore, a study was conducted to evaluate the water stress tolerance in young saplings of Syzygium cumini (L.) Skeels and Populus deltoides Marchall that are cultivated in the rain fed areas of Pakistan. Plants were subjected to three levels of moisture regimes: well-watered (WW, 90% of field capacity), mild stress (MS, 60% field capacity), and severe stress (SS, 30% of field capacity). Results showed that dry biomass production (leaf, stem, and root), chlorophyll a, b and carotenoid contents decreased significantly while osmolyte accumulation increased in both species, with the highest increase was evidenced in Populus deltoides saplings. A significant decrease was evidenced in CO2 assimilation rate and stomatal conductance that resulted in a significant increase in intrinsic water use efficiency in both species under MS and SS. In both the species, along with a significant increase in the production of hydrogen peroxide and superoxide radical, the antioxidants enzyme activities of superoxide dismutase, peroxidase, catalase, and ascorbate peroxidase also increased significantly in both species under MS and SS with highest activity evidenced in Syzygium cumini. The results suggest that Syzygium cumini saplings showed better a tolerance mechanism to water stress.